2006
DOI: 10.1292/jvms.68.881
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Salmonella Isolates from Apparently Healthy Food-Producing Animal from 2000 to 2003: the First Stage of Japanese Veterinary Antimicrobial Resistance Monitoring (JVARM)

Abstract: ABSTRACT. Antimicrobial susceptibility of 183 Salmonella isolates from apparently healthy food-producing animals obtained during the period from 2000 to 2003 throughout Japan was examined. Of 29 serovars identified, Salmonella Infantis (37.7%) was the most prevalent, followed by S. Typhimurium (19.7%). Salmonella bacteria resistant to dihydrostreptomycin (77.6%) were about 10% more prevalent than those resistant to oxytetracycline (67.8%), though the nation-level veterinary use of tetracycline antibiotics is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 15 publications
7
28
0
Order By: Relevance
“…Surprising results that was no difference between inhibition zones of methicillin-resistant and methicillin-susceptible strain may be due to the some component of essential oil caused bacterial cell damaged this result is in agreement with [44][45][46]. They found that essential oil caused gross membrane damaged and provoke whole cell lysis of eukaryotic.…”
Section: Discussionsupporting
confidence: 60%
“…Surprising results that was no difference between inhibition zones of methicillin-resistant and methicillin-susceptible strain may be due to the some component of essential oil caused bacterial cell damaged this result is in agreement with [44][45][46]. They found that essential oil caused gross membrane damaged and provoke whole cell lysis of eukaryotic.…”
Section: Discussionsupporting
confidence: 60%
“…enterica serovar Typhimurium. Asai et al [1] reported similar results in that the prevalence of Salmonella in beef cattle was 2.5% (16/650) and the predominant serovar was S. Typhimurium, suggesting that the results of the present study are compatible with those of Asai et al [1]. In the present study, although samples were obtained from 10 healthy dairy cows without clinical signs of salmonellosis, eight of the animals tested on one farm were positive for S. Typhimurium.…”
supporting
confidence: 90%
“…Fresh faecal samples were collected from apparently healthy cattle, pigs and layer and broiler chickens throughout the country as previously described [2]. E. coli, E. faecalis and E. faecium were isolated from faecal samples as previously described [11,13].…”
Section: Methodsmentioning
confidence: 99%